Microstructure, phase structure, and electrical properties of nitrided 3 mol% Y2O3 stabilized ZrO2 (3YSZ). Issue 3 (15th February 2019) - Mo, Yangcheng; Liu, Tao; Wang, Xiangnan; Li, Jingyun; Yi, Maoyi
Abstract: 3 mol% Y2 O3 stabilized monoclinic and tetragonal ZrO2 (3YSZ) was prepared by a co-precipitation method. When the sintered 3YSZ samples were embedded into ZrN powder and heat-treated at different temperatures (1300–1500 °C) in flowing nitrogen gas, nitrided 3YSZ (3YSZ-N) was formed. The microstructure, phase structure, ionic conductivity, and electronic conductivity were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), electrochemical impedance spectroscopy (EIS), and Hebb-Wagner method, respectively. The results showed that the grain-boundary of tetragonal phase 3YSZ-N was difficult to be observed. Above 700 °C, the conductivity of 3YSZ-N was higher than that of 3YSZ, and increased with the increase in nitrogen content. The electronic conductivity of 3YSZ-N decreased and then increased with the increase of nitrogen content. The thermogravimetric and differential scanning calorimeter analyses (TG-DSC) showed that 3YSZ-N was oxidized in air above 600 °C.